Education for the year 2000 - focus on children of poverty - Barrozo, Aurora C. (Education Quarterly, 1992)
The paper shares several studies on the effectivity of the California Compensatory Education Projects mostly coordinated by the writer. The results of these and other related studies on education and poverty evolve the blueprint of the so-called "Dream School" for the start of the next millennium which is not without great challenges for the educator.